Experiencing wireless sensor network deployments : data dissemination and remote control - Chua, Eileen Zhi Ting. (2012)
When wireless sensor networks (WSNs) are being deployed, the WSN systems often failed to provide the expected results. Therefore, by using the various data dissemination and remotes control schemes that are being implemented in TinyOS to find out about the advantages and disadvantages of the schemes available.